Development of a Fuzzy Logic Health Index for Generator Stator Insulation Condition Assessment - Muhamad Arief Afandy; Agung Trihasto; Risky Via Yuliantari (Institut Teknologi Dirgantara Adisutjipto, 2026)
Stator insulation breakdown is the primary cause of generator failures, driven by cumulative thermal, electrical, and mechanical stresses. For generator Unit 2 at PLTU Palabuhan Ratu Coal-Fired Power Plant, the Mamdani fuzzy logic model provides an automated, rule-based diagnostic assessment utilizing tip-up tan delta, AC leakage current, and partial discharge measurements. This model predicts the Health Index of generator phases using historical test data 2019, 2023, and 2025. It successfully classifies phases R, S, and T into the